An efficiency virtual resource auction mechanism based on reserve-price strategy in cloud environments. (3rd March 2020) - Xiao, Peng
In economic-based cloud models, resource pricing mechanism plays a key role to regulate the supply and demand for resources, provides an incentive for providers, and motivates the users to trade-off between deadline, budget, and the required level of quality of service. In this paper, we formulate the problem of resource auction as a distributed constrained programming problem; then we propose an effective and efficient auction algorithm, which use reserve-price strategy to guarantee that users pay at least a given amount determined by cloud providers. In this way, we can significantly improve the efficiency of auction process as well as provide sufficient incentive for cloud providers to share their spare resources. To evaluate the proposed auction algorithm, extensive experiments are conducted in a real-world cloud platform, and the results indicate that it can significantly increase the provider revenue as well as improve the quality-of-service (QoS) satisfactory.